Las cient novelas de Juan Bocacio: a critical edition of the medieval Castilan translation of Boccaccio's Decameron - Di Dodo, E (2023)
This thesis is a critical edition of the fifteenth-century Castilian translation of Boccaccio’s Decameron, based on Alberto Blecua’s neo-Lachmannian methodology: the first part presents the results of the recensio process, and the second is the critically edited text with the critical apparatus and linguistic variants. Due to the length of the text and the attention to detail required when preparing a critical edition, this thesis covers the first half of the text in the printed tradition (tabla, prologue, introduction and novelle I-LI).